2016
DOI: 10.1002/ange.201605405
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning of the Ferroelectric Phase in a Poly(vinylidene difluoride) Film by Plasmonic Heating with Gold Nanocages

Abstract: Polymer thin films with patterned ferroelectric domains are attractive for ab road range of applications, including the fabrication of tactile sensors,i nfrared detectors, and non-volatile memories.H erein, we report the use of gold nanocages (AuNCs) as plasmonic nanostructures to induce af erroelectric-paraelectric phase transition in ap oly(vinylidene fluoride) (PVDF) thin film by leveraging its photothermal effect. This technique allows us to generate patterned domains of ferroelectric PVDF within just afew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For the AuNC/PVDF nanofibers, the strong absorption in the range of 300āˆ’500 nm can be attributed to PVDF and/or the nanofiber morphology. 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the AuNC/PVDF nanofibers, the strong absorption in the range of 300āˆ’500 nm can be attributed to PVDF and/or the nanofiber morphology. 17…”
Section: Resultsmentioning
confidence: 99%
“…8ā€“11 In addition, the polymer chains can also be aligned to obtain the Ī² phase when PVDF is dissolved in a mixture of acetone and N, N-dimethylformamide (DMF), and electrospun into nanofibers by leveraging the strong electrical field and mechanical stretching force associated with electrospinning. 12ā€“14 Moreover, it has been reported that the incorporation of nanoparticles made of materials such as Ag, 15,16 Au, 17ā€“19 and ZnO 20 could play a positive role in aligning the polymer chains and thus enhancing the piezoelectric response. It was proposed that the strong electrostatic interactions between the positively charged nanoparticles and the negatively charged fluorine atoms in the polymer backbone could produce interfacial polarization on the crystalline phase to facilitate the formation of the Ī² phase.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various structural designs of pyroelectric materials (e.g., micropatterning and microchannels) using micromanufacturing and/or sand blasting techniques have been proposed to enhance heat transfer by convection or radiation in PVDF thin films 64,65 and PZT ceramics [66][67][68][69][70][71][72] in order to improve the energy conversion efficiency of materials and devices. Note that reducing the sample thickness should not change the energy per volume N D achieved under quasiequilibrium conditions.…”
Section: Methodsmentioning
confidence: 99%
“…We then investigated the photothermal conversion efficiency of BPBBT molecules in coreā€“shell fiber and their durability. The photothermal conversion efficiency could be calculated by following equation: [28] trueQ=c0.166667emm0.166667emĪ”T …”
Section: Figurementioning
confidence: 99%